Duration of active epilepsy as a predictor of seizure control after relapse in child epilepsy - Charles Subakti; Madarina Julia; Agung Triono (Paediatrica Indonesiana, 2020)
Background Epilepsy is a chronic illness that may affect childhood growth and development. Some epilepsy cases are easy to control, either with monotherapy or politherapy antiepilepticdrugs, but many cases are difficult to control. Several factors influence the risk of relapse, but information is limited on factors predictive of seizure control after relapse. Our study investigate patient with epilepsy relaps and see whether the duration of active epilepsy prior to initial remission can be use as a predictor of seizure control after relaps. Objective To assess whether duration of active epilepsy was predictive of seizure control after relapse. Methods This retrospective cohort study was performed in Dr Sardjito Hospital, Yogyakarta, on epileptic relapse patients aged 2 to 18 years , who had achieved remission for at least a 2-year seizure-free interval, and relapsed after antiepileptic drud (AED) discontinuation. We excluded patients with progressive neurological diseases, inborn errors of metabolism, febrile seizures, and those who could not be followed up for at least 2 years, or those with incomplete medical records. Subjects were divided into those who had a duration of active epilepsy prior to initial remission within 6 months and â‰¥6 months. Time to seizure control after relapse was analysed by Kaplan-Meier survival analysis. Results A total of 80 patients were included in the study. Overall median for seizure control after relapse was 3.6 (95%CI 1.1 to 6.0) months. Median for seizure control after relapse for those who had a duration of active epilepsy prior to initial remission within 6 months and >= 6 months were 3 (95%CI 0.1 to 5.8) months and 12 (95%CI 4.4 to 19.5) months, respectively. Log-rank test revealed no significant difference between groups (P=0.12). Conclusion Duration of active epilepsy prior to initial remission was not a predictor for seizure control after relapse.